La poesia catalana dels anys seixanta i els diversos usos del realisme - Aulet, Jaume (Caplletra. Revista Internacional de Filologia, 2000)
Resum: This essay presents a revisión of the Catalan poetry of the 1960s linked to the historical realism, starting from the different ideas and heterogeneous formulations at that time. After introducing the divergent positionings of the critics, the essay revises the poetic programme from the making up of an action-taking discourse as planned by ideologists, from the making up and tuming-into-myth of poetic models, from the recovery of a given tradition such as that of Salvat-Papasseit, and from the existence of platforms of dissemination. Then follows a more exhaustive analysis of the various kinds of realism in the poetry of the writers of the 1960s. Paraules clau: poesia catalana: anys seixanta; realisme; Joan Salvat-Papasseit